Food packaging : Principles and practice - Robertson, Gordon L. (Florida CRC Press, 2012)
This book presents a comprehensive and accessible discussion of food packaging principles and their applications. Integrating concepts from chemistry, microbiology, and engineering, rovide a detailed overview of contemporary food packaging technologies.
Includes bibliographical references and index.
Keywords: Công nghệ thực phẩm